Ecotoxicological consequences of polystyrene naturally leached in pure, fresh, and saltwater: lethal and nonlethal toxicological responses in Daphnia magna and Artemia salina - Esterhuizen, Maranda; Lee, Sang-Ah; Kim, Youngsam; Järvinen, Riikka; Kim, Young Jun (Frontiers in Marine Science, 2024)
Polystyrene is widely used in disposable products and is now a ubiquitous plastic pollutant in aquatic environments, where it degrades into smaller particles that leach potentially toxic chemicals. However, knowledge regarding the impacts of plastic leachates remains limited. This study investigates the lethal and nonlethal effects of polystyrene leachate on two ecologically significant aquatic organisms, Daphnia magna (water flea) and Artemia salina (brine shrimp). Polystyrene leachates were prepared in seawater, freshwater, and sterile, pure water by incubating the material in each of the media under natural conditions for six months. D. magna and A. salina were exposed to varying concentrations of the leachates under controlled laboratory conditions, monitoring their survival, as well as measuring reactive oxygen species and antioxidant responses as superoxide dismutase and catalase activity. The data show that A. salina was more significantly affected with higher mortality observed at lower leachate concentrations, potentially linked to seawater enhancing the leaching of toxic additives. Moreover, at non-lethal concentrations, the antioxidative responses maintained homeostasis in both organisms. Considering the current reported microplastic concentrations in the aquatics and the adequate antioxidative response, leachate from plastic potentially does not pose a severe threat to these organisms. Nevertheless, hydrological characteristics of waterbodies may cause microplastic hotspots, which could significantly concentrate plastics and thus their leachates, necessitating action to reduce the current microplastic pollution level and avoid future surges. This study highlights the ecological significance of polystyrene pollution, emphasizing the need for more comprehensive regulatory measures and the development of sustainable alternatives to polystyrene-based products. The distinct responses of D. magna and A. salina imply that the impact of plastic pollution varies among species, necessitating further research to elucidate broader ecological consequences. Understanding how polystyrene leachate affects keystone species provides crucial insights into the overall implications for aquatic ecosystems.